الدعوة الفردية وأثرها في التغير والإصلاح من خلال السيرة النبوية - موساوي, نور الهدى; عوينات, خلود; قدة, كريمة (University of Eloued-جامعة الوادي, 2022)
"ملخص الدراسة: تهدف هذه الدراسة إلى توضيح مكانة الدعوة الفردية في الدعوة إلى الله ودين الحق، كما تناولت هذه استنباط لمختلف الأساليب النبوية في الدعوة إلى الله، حيث قمنا بتتبع هذه الأساليب من خلال الأحاديث النبوية والقرآن الكريم، لنصل إلى الأثر الذي يتركه الداعي في نفس المدعو من خلال الاقتداء بسنة النبي  وبذلك التوجه نحو التغيير ومنه إصلاح الأمم والمجتمعات. ""ABSTRACT This study aims to clarify the place of individual advocacy in the call for God and the religion of truth. It also devised various prophetic methods in the call for God. We tracked these methods through prophetic conversations and the Holy Koran, in order to reach the impact that the advocate has on the same invitation by imitating the Year of the Prophet thus moving towards change and reforming nations and societies."
مذكرة ماستر
Keywords: لدعوة الفردية - أثرها - التغيير والإصلاح - السيرة النبوية; The individual call - its impact - change and reform - the biography of the Prophet